ANALISIS PENINGKATANDAN PENGEMBANGAN MUTU PELAYANAN DENGAN QUALITY FUNCTION DEPLOYMENT PADA PT PKP BATAM - Panjaitan, Agustina erista; Sumantika, Arsyad (LPPM Universitas Putera Batam, 2023)
The purpose of this research is to find out how far the QFD (Quality Function Deployment) method has been implemented at PT PKP Batam, to find out how the QFD (Quality Function Deployment) method has been implemented at PT PKP Batam, and the House of Quality Matrix. This research is a case study conducted by collecting data through observation, questionnaires, interviews and documentation. PT PKP's Customer Research Target and Existing Customers. Quantitative data was arranged descriptively using Microsoft Excel and SPSS programs. The results of the study show that PT PKP implements QFD (Quality Functional Deployment). Consumer needs at PT PKP Batam which are considered very important are: the accuracy of the work of workers, the professionalism of workers, the skilled ability of workers to serve customers, the number of workers compared to the construction of residential houses, the perfection of equipment, the speed of work of workers, the quality of the buildings submitted, the quality of construction is guaranteed, construction insurance, a sense of security of the building occupied, PT. PKP is fully responsible for the results of the construction, polite and friendly service, complete entertainment services in the waiting room, cleanliness. waiting room and waiting room comfort. Assessment of consumers of PT.PKP services with a score of 1.851 with priority 1 Construction Insurance with a score of 0.531 with priority 11.